Effects of rotary cell culture system‐simulated microgravity on the ultrastructure and biological behavior of human MDA‐MB‐231 breast cancer cells. Issue Volume 3:Issues 3(2019) (4th September 2019) - Jiang, Nan; Chen, Zhengyang; Li, Binbin; Guo, Song; Li, Ao; Zhang, Tao; Fu, Xiaoyan; Si, Shaoyan; Cui, Yan
Abstract: Objective: This study aimed to investigate changes in the ultrastructure, apoptosis, cycle progression, and migration ability of human MDA‐MB‐231 breast cancer cells under simulated microgravity conditions. Methods: MDA‐MB‐231 breast cancer cells were cultured in a rotary cell culture system bioreactor to simulate microgravity for 7 days. The cells were randomly divided into a simulated microgravity (SMG) group and normal gravity control (NG) group. Changes in apoptosis, ultrastructure, cell cycle, and migration ability were evaluated. Results: Transmission electron microscopy showed that cells in the SMG group had more secondary lysosomes than the NG groups. The flow cytometry assay showed that the proportion of apoptotic cells in the SMG group was significantly increased compared with the NG group; additionally, the median and interquartile spacing of the proportion of cells in the G0/G1 phase in the SMG group was lower than in the NG group, but the proportion of cells in the S phase was increased in the SMG group compared with the NG group. The transwell migration assay showed that cell migration in the SMG group was significantly reduced compared with the NG group. The expression of BCL‐2 and MMP9 in the SMG group was decreased compared with the NG group, whereas the expression of cyclin D3 in the SMG group was increased. Conclusion: Simulated microgravity through rotary cell culture system had significant effects on human MDA‐MB‐231 breast cancer cells: the cell cycle and ultrastructure were impaired, apoptosis increased, migration ability decreased, and the expression of BCL‐2, cyclin D3, and MMP9 were affected.